Association of limited English proficiency and increased pediatric emergency department revisits. (25th August 2021) - Portillo, Elyse N.; Stack, Anne M.; Monuteaux, Michael C.; Curt, Alexa; Perron, Catherine; Lee, Lois K.
Abstract: Objective: Limited English proficiency (LEP) is a risk factor for health care inequity and an important focus for improving communication and care quality. This study examines the association between LEP and pediatric emergency department (ED) revisits. Methods: This was a retrospective, cross‐sectional study of patients 0 to 21 years old discharged home after an initial visit from an academic, tertiary care pediatric ED from January 1, 2017, to June 30, 2018. We calculated rates of ED revisits within 72 h resulting in discharge or hospitalization and assessed rate differences between LEP and English‐proficient (EP) patients. Multivariable logistic regression models examined the association between revisits and LEP status controlling for age, race, ethnicity, triage acuity, clinical complexity, and ED arrival time. Sensitivity models including insurance were also conducted. Results: There were 63, 601 index visits in the study period; 12, 986 (20%) were by patients with LEP. There were 2, 387 (3.8%) revisits within 72 h of initial ED visit. Among LEP and EP patient visits, there were 4.53 and 3.55 revisits/100 initial ED visits, respectively (rate difference = 0.97, 95% confidence interval [CI] = 0.58 to 1.37). In the multivariable analyses, LEP was associated with increased odds of revisits resulting in discharge (odds ratio [OR] = 1.15, 95% CI = 1.01 to 1.30) and in hospitalization (OR = 1.28, 95% CI = 1.03 to 1.58). Sensitivity analyses additionally adjusting for insurance status attenuated these results. Conclusions: These results suggest that LEP was associated with increased pediatric ED revisits. Improved understanding of language barrier effects on clinical care is important for decreasing health care disparities in the ED.